2019
DOI: 10.1002/joom.1066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of customers' digital banking adoption on hidden defection: A combined analytical–empirical approach

Abstract: The implementation of digital channels as avenues for economic transactions (e.g., online and mobile banking/FinTech) has shifted the paradigm of customer–bank interactions, providing unprecedented opportunities for both parties. The prevailing belief is that digital banking has several advantages, such as lower costs and higher information transferability for customers. These benefits can also promote competition between banks given customers' predilection for “multi‐homing,” or engagement with multiple banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 82 publications
1
32
0
Order By: Relevance
“…New communication technologies allowed for the rapid advancement of digital banking service channels and became responsible for the emergence of new products and services, benefiting banks and customers with agility, ease and cost reduction (Romanova et al, 2018;Son et al, 2019). These same new technologies have made it easier for customers to access new banking service providers, and it is now more common to have relationships with more than one bank, being able to easily choose where to execute their financial transactions (Son et al, 2019).…”
Section: Engagement In Digital Service Channelsmentioning
confidence: 99%
“…New communication technologies allowed for the rapid advancement of digital banking service channels and became responsible for the emergence of new products and services, benefiting banks and customers with agility, ease and cost reduction (Romanova et al, 2018;Son et al, 2019). These same new technologies have made it easier for customers to access new banking service providers, and it is now more common to have relationships with more than one bank, being able to easily choose where to execute their financial transactions (Son et al, 2019).…”
Section: Engagement In Digital Service Channelsmentioning
confidence: 99%
“…Consequently, the above phenomenon forms an intense competition among Islamic bank institutions (Suhartanto et al, 2019), and changes customers' points of view of service quality presented by banks (Son et al, 2019). Moreover, Saptasari & Aji (2020) discovered that perceived quality play a prominent role in shaping customer satisfaction towards Islamic bank in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…branch visits) users, compared with self-service channel (e.g. ATM, phone banking) users (Son et al, 2020). Second, omnichannel retail indirectly improves consumer loyalty through increasing product satisfaction (Gallino et al, 2017).…”
Section: Omnichannel Research In Marketing 41 Consumer Behaviors In Omnichannel Retailmentioning
confidence: 99%
“…Current studies have suggested some opportunities regarding marketing in omnichannel research (Fisher et al, 2019;Luo et al, 2020;Son et al, 2020;Song et al, 2020;Valentini et al, 2020). The first direction is to use data at a finer level to understand the mechanisms of omnichannel consumer behaviors induced by omnichannel practices.…”
Section: Research Opportunities For Marketingmentioning
confidence: 99%
See 1 more Smart Citation